The attractiveness of the project of practical methodology and virtue epistemology for the economic history research - Bębnowski, Damian (Annales. Etyka w Życiu Gospodarczym, 2019)
Ewa Domańska, a distinguished historian of historiography and the methodologist of history, has provided an insightful commentary on the state of humanities and social sciences. The development of interdisciplinary research in social sciences and humanities has resulted in varying outcomes and interpenetrations. Interdisciplinary research helps the development of science. However, studies undertaken with less rigor may pose some threats into the long term. According to Domańska, the lack of qualifications and care (especially with respect to theory and methodology) may undermine the autonomy of a disciplines and the credibility of research in the given field. This timely warning prompted the author to create the project with the aim to assert the independence of the threatened disciplines and to “re-professionalize” these areas of study. This is to be achieved by emphasizing the role of theory in science—a strong embeddedness of a discipline in the theory. Domańska’s concept, in the form of a dichotomous project, seems to be a recipe for achieving this goal. It presupposes, on the one hand, a “practical methodology”, i.e. constructing the theory basing on empirical research material, and on the other hand the so-called “virtue epistemology”, which stresses an ethical aspect of the researcher’s attitude and labour. The aim of the paper is to discuss Domańska’s project and to draw attention to the originality of her concept in the context of economic and social sciences. The economic history is a peculiar discipline founded at the intersection of history and economics. Thus, it is possible to put forward the thesis that Domańska’s suggestions are relevant to the research of economic history. The author will seek to determine what cognitive opportunities arise from the ontology of economic history and their potential threats to the main disciplines of history and economics. The article will also examine if Domańska’s project is appropriate for the economic history research as it is deeply embedded in “practical methodology”, and so in theory. Next, the author aims to consider the role of new theoretical approaches in this field, and whether it is possible to formulate novel concepts within the scope of the economic history. Finally, the author will attempt to assess the significance of “virtue epistemology” or the ethical aspect of an economic historian’s work.